A Simple Way Constructing Symplectic Runge-Kutta Methods (Journal of Computational Mathematics, 2000)
With the help of symplecticity conditions of Partitioned Runge-Kutta methods, a simple way constructing symplectic methods is derived. Examples including several classes of high order symplectic Runge-Kutta methods are given, and showed up the relationship between existing high order Runge-Kutta methods.
Keywords: Symplecticity condition; Partitioned Runge-Kutta method.